Sources of productivity growth at the firm level: A production function approach - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1997)
In the paper, the sources of productivity growth are investigated by an empirical analysis with micro data for West-German manufacturing firms. The theoretical framework corresponds to an augmented growth accounting approach based on a production function. The empirical results reveal that innovative firms exhibit more productivity increases. Large firms exhibit more productivity increases as compared with small firms, ceteris paribus, which hints towards scale economies at the firm level. However, innovations seem to be more productive in small firms. Scale economies at the sectoral level are indicated by positive spillover effects from others productivity changes.
Keywords: C33; O39; 330; Growth accounting; innovations; Produktivität; Wirtschaftswachstum; Produktionsfunktion; Unternehmen; Innovation; Skalenertrag; Spillover-Effekt; Deutschland; Investition